PUDARNYA JATI DIRI ARSITEKTUR KHAS INDONESIA (Studi Kasus Bangunan-bangunan Dengan Penerapan Arsitektur Rumoh Aceh di Kota Lhokseumawe) - Dela Andriani; Erna Muliana; Sisca Olivia (Vastutara : Arsitektur, Digital, Sejarah, Struktur dan Lingkungan, 2025)
The Development of modernization and rapid development of architecture give wide opportunity for foreign culture's value to set in. That values influence the development of archipelago architecture and shift the nation vales of culture as the foundation of Indonesian architectural identity. The shift that is finally fading out the values of traditional architecture that has been manifested in society life. Aceh house or Rumoh Aceh is traditional house of Nanggroe Aceh Darussalam which is a part of the culture that manifested from space. Currently, only few rumoh aceh can be found in Nanggroe Aceh Darussalam. This is partly caused by the development of times. This study aims to find the causes and things that affect the fade of Indonesia traditional architecture with the case studies of the application of Rumoh Aceh architecture on buildings in some areas in Aceh.